"Reliving my Childhood Dream of being a Pokémon Trainer": An Exploratory Study of College Student Uses and Gratifications Related to Pokémon Go. Issue 7 (21st April 2019) - Vaterlaus, J. Mitchell; Frantz, Kala; Robecker, Tracey
ABSTRACT: Pokémon Go is an interactive mobile game that was launched in July 2016. The current exploratory study recruited college students ( n = 278) who currently played, no longer played, or had never played Pokémon Go to understand their lived experiences with this game and determine differences in perceived behavioral outcomes of playing between current and past players. The research team implemented a Uses and Gratifications (U&G) theoretical framework and qualitative research design. Three themes were identified through qualitative content analysis and included: (a) limitations to playing Pokémon Go, (b) motivations for playing Pokémon Go, and (c) social consequences of playing Pokémon Go. Results are discussed in connection with U&G.